2022
DOI: 10.21037/atm-21-6295
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of distant metastasis and survival prediction of gastric cancer patients with metastasis to the liver, lung, bone, and brain: research based on the SEER database

Abstract: Background: Gastric cancer (GC) is a globally important disease. It is the 5th most common malignancy and the 4th most common cause of death from cancer in the world. Patients with GC are often at an advanced stage when they are first diagnosed, and their overall prognosis is poor due to locally advanced and distant metastasis. This study sought to establish a predictive model of GC distant metastasis and survival that can be used to guide individualized treatment.Methods: Patients diagnosed with GC from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
(42 reference statements)
2
18
0
Order By: Relevance
“…In our study, we found that patients with advanced gastric cancer with bone metastasis, liver metastasis and lung metastasis had a signi cantly higher risk of death than patients without these site metastases. This is similar to the phenomenon observed by a previous study on SEER databases (9). Compared with patients without brain metastasis, although the risk of death increased in patients with brain metastasis, but the con dence interval of 95% HR crossed 1, so there was no statistical difference.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we found that patients with advanced gastric cancer with bone metastasis, liver metastasis and lung metastasis had a signi cantly higher risk of death than patients without these site metastases. This is similar to the phenomenon observed by a previous study on SEER databases (9). Compared with patients without brain metastasis, although the risk of death increased in patients with brain metastasis, but the con dence interval of 95% HR crossed 1, so there was no statistical difference.…”
Section: Discussionsupporting
confidence: 90%
“…Another research used the SEER database of 640 patients with lung metastasis of gastric cancer to construct a nomogram to predict overall survival, but did not involve patients with other metastatic sites(8). Zikai et al (9) used SEER database to establish a nomogram to predict the prognosis of gastric cancer with different metastatic sites (liver, lung, bone, brain), but regrettably, surgery for primary site, chemotherapy, radiotherapy and other prognostic factors were not included in the analysis. Therefore, there is an urgent need to establish a model that includes more factors to predict the prognosis of stage IV gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study showed that in patients with early-onset GC, the size of the tumor, the total number of lymph nodes removed during surgery, the T4 and N3 tumor stages, and therapeutic interventions without radiation and chemotherapy were associated with the development of DM after surgery. Tumor grade, primary tumor diameter, T stage, and N stage were found to be predictors of synchronous DM in GC by Zikai Lin et al (16). In accordance with the prior study, and we also included the size of the tumor, T stage, and N stage in our model.…”
Section: Radiationmentioning
confidence: 74%
“…In 2020, cancer caused 10 million deaths in the world, and GC accounted for 7.7% (770,000), ranking the fourth cause of death after lung cancer, colorectal cancer, and liver cancer [ 1 ]. Although there are various treatments for GC, the survival rate of many advanced GC patients with metastasis, recurrence, and chemotherapy is quite low [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Therefore, new therapies are urgently required to improve the survival rate of advanced GC patients.…”
Section: Introductionmentioning
confidence: 99%